Relationship between serotonin transporter gene polymorphism and constipation in cancer patients - Li, Weiwei; Huang, Luli; Cai, Weimei; Cao, Sue; Yuan, Yan; Lu, Sheng; Zhao, Yanzheng; Lu, Ping (Contemporary Oncology/Współczesna Onkologia, 2015)
Introduction : To assess the potential association between serotonin transporter gene insertion/deletion polymorphism and the cancer-related constipation phenotype. Material and methods : A total of 120 patients diagnosed with malignant solid tumors were subjected to genotyping. For the two groups – patients with constipation and constipation-free patients with non-gastrointestinal cancer, 60 cases in each group – we collected the peripheral venous blood. We extracted genomic DNA, and used polymerase chain reaction (PCR) to analyze the serotonin transporter (5-HT) link polymorphic region (5-HTTLPR) polymorphism of the serotonin transporter gene. Results: The frequency of S/S genotype in cancer patients with constipation was 66.67% (40/60), and the frequency of the S allele was 79.17% (95/120); the frequency of S/S genotype in cancer patients without constipation was 48.33% (29/60), and the frequency of the S allele was 65.83% (79/120). There was a significant difference between the two groups (p < 0.05). Conclusions : The presence of 5-HTTLPR S/S genotype and the S allele in patients with cancers probably carry an increased risk of constipation. However, its role as a cause of cancer-related constipation needs to be further investigated.